2008
DOI: 10.1080/15257770802136040
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Hyperuricemia: Impact of Ultrasonography

Abstract: Thirty-five patients (23 males) with asymptomatic hyperuricemia for at least two years underwent two-dimensional ultrasonography of knees and ankles. Urate deposits (tophi) in tendons, synovium, and other soft tissues were detected in 12 patients (34%). Increased vascularity (inflammation) was evident in 8 of these patients (23%). Tophi were more frequently found in knees than in ankles and were especially prevalent in the distal patellar tendon. The presence of tophi was unrelated to the known duration of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 8 publications
4
60
1
4
Order By: Relevance
“…In comparison to DECT, US appears to be more feasible because it is patient-friendly, safe and non-invasive, free of ionizing radiation, allows multiple target assessment in real time, and may aid the aspiration process for relevant material for microscopy 7 . Several published studies have highlighted the ability of US to detect crystal deposits and have addressed its possible role in very early diagnosis, based on their US findings indicative of gout in patients with asymptomatic hyperuricemia 7,8,9 .…”
mentioning
confidence: 99%
“…In comparison to DECT, US appears to be more feasible because it is patient-friendly, safe and non-invasive, free of ionizing radiation, allows multiple target assessment in real time, and may aid the aspiration process for relevant material for microscopy 7 . Several published studies have highlighted the ability of US to detect crystal deposits and have addressed its possible role in very early diagnosis, based on their US findings indicative of gout in patients with asymptomatic hyperuricemia 7,8,9 .…”
mentioning
confidence: 99%
“…Ottaviani et al [34] detected articular urate deposits in 60% of gouty patients (the prevalence of tophi for knees and MTPs being 26.7%), more common in patients with higher serum uric acid. The tophi were found as well in patients with asymptomatic hyperuricaemia not only in synovium but also in tendons and soft tissue [45,46].…”
Section: Msu Aggregates (Hyperechoic Spots Hyperechoic Cloudy Areasmentioning
confidence: 84%
“…Among the periarticular bursae, the pre-patellar and olecranon bursae are the most commonly involved sites [46,49]. Fernandes et al [51] found that hyperechogenicity (91.7%), poorly defined contours (88.6%), multiple grouped nodules (85.6%), and heterogeneity (68.6%) are the most characteristics findings of the tophi from olecranon bursa.…”
Section: Msu Aggregates (Hyperechoic Spots Hyperechoic Cloudy Areasmentioning
confidence: 99%
“…MRI has been shown to be of value when evaluating synovial involvement, but at higher cost to the patient 6 . Ultrasonography may suggest early deposition of uric acid crystals and may reveal synovial thickening and inflammation but its use is largely limited to peripheral joints 7 . Although ultrasonography and CT may assist in direct aspiration of a joint for crystal evaluation, neither can specifically identify uric acid crystal deposition.…”
Section: To the Editormentioning
confidence: 99%